Breaking Dawn Part 1: Sebuah Analisa tentang Egoisme - Putra, Febby Pratama; Desnaranti, Laila (LITERATUS, 2024)
The objective of the study is to examine the egoism exhibited by the protagonist in the film Breaking Dawn Part 1, directed by Bill Condon. In addition, the writer seeks information regarding internal and external problems as well as moral lessons. The methodology involves conducting library research and extracting relevant data from the movie. To complete the analysis, the writer employs theoretical concepts derived from Hill and Fieser.The study reveals that the primary character's egoism stems from a deficiency in realistic objectives, a tendency towards antisocial behavior, and a lack of self-control. Bella's primary concern is her own well-being in order to protect her child. The primary character exhibits two sorts of character traits: psychological egoism and ethical egoism. The internal struggles revolve around the decision to embrace vampirism and the choice between prioritizing personal safety or the continuation of her pregnancy. The external conflict arises from Jacob's opposition to Bella's refusal of his advice and the clash between Bella's firm determination and the opposing views of the Cullen family. The movie effectively conveys the varying degrees of egoism exhibited by individuals in social interactions. Effective socialization occurs when individuals prioritize the interests of others over their interests.